The many meanings of collective action: lessons on enhancing gender inclusion and equity in watershed management - German, Laura; Taye, Hailemichael; Charamila, Sarah; Tolera, Tessema; Tanui, Joseph (International Food Policy Research Institute, 2006)
Collective action in agriculture and natural resource management is all too often perceived of in terms of the mere number of participants, with little consideration given to who participates, why, and the outcomes of inequitable participation. The literature is replete with cases of how uncritical approaches to participation structure positions of privilege vis-à-vis project benefits and the natural resource base. Yet lessons on how to engage with local communities in ways that promote equitable participation of women, the poor and other stakeholders are only now coming to light. This paper focuses on approaches under development under the rubric of the African Highlands Initiative to bring collective action principles to bear on gender-equitable change processes in natural resource management. The paper utilizes a number of case studies to illustrate the relative strengths and weaknesses of different approaches for enhancing gender inclusion and equity throughout the stages of problem diagnosis, planning and monitoring. The analysis suggests that an arbitrary definition of collective action is insufficient for assessing the relative strengths and weaknesses of different approaches, and that method evaluation should consider the different forms that collective action can take. A typology of different forms of collective action is proposed, and then utilized to assess the relative strengths and weaknesses of different approaches for fostering gender inclusion and equity in watershed management.